K2 Optical Emission from OJ 287 and Other γ-Ray Blazars on Hours-to-weeks Timescales from 2014 to 2018 - Ann E. Wehrle; Michael Carini; Paul J. Wiita; Joshua Pepper; B. Scott Gaudi; Richard W. Pogge; Keivan G. Stassun; Steven Villanueva Jr. (The Astrophysical Journal, 2023)
We present second observations by K2 of OJ 287 and seven other γ -ray active galactic nuclei (AGNs) obtained in 2017–2018, second and third observations of the lobe-dominated, steep-spectrum quasar 3C 207, and observations of nine additional blazars not previously observed with K2. The AGNs were observed simultaneously with K2 and the Fermi Large Area Telescope for 51–81 days. Our full sample, observed in 2014–2018, contained 16 BL Lacertae objects (BL Lacs), nine flat-spectrum radio quasars (FSRQs), and four other γ -ray AGNs. Twelve BL Lacs and seven FSRQs exhibited fast, jagged light curves, while four BL Lacs and two FSRQs had slow, smooth light curves. Some objects changed their red-noise character significantly between repeated K2 observations. The optical characteristics of OJ 287 derived from the short-cadence K2 light curves changed between observations made before and after the predicted passage of the suspected secondary supermassive black hole through the accretion disk of the primary supermassive black hole. The average slopes of the periodogram power spectral densities of the BL Lacs’ and FSRQs’ light curves differed significantly, by ≈12%, with the BL Lac slopes being steeper, and a Kolmogorov–Smirnov test with a p -value of 0.039 indicates that these samples probably come from different populations; however, this result is not as strongly supported by power spectral response (PSRESP) analyses. Differences in the origin of the jets from the ergosphere or accretion disk in these two classes could produce such a disparity, as could different sizes or locations of emission regions within the jets.